The use of QBO, ENSO, and NAO perturbations in the evaluation of GOME-2 MetOp A total ozone measurements - Eleftheratos, Kostas; Zerefos, Christos S.; Balis, Dimitris S.; Koukouli, Maria-Elissavet; Kapsomenakis, John; Loyola, Diego G.; Valks, Pieter; Coldewey-Egbers, Melanie; Lerot, Christophe; Frith, Stacey M.; Søvde, Ole Amund; Isaksen, Ivar S A; et al. (Atmospheric Measurement Techniques, 2019)
In this work we present evidence that quasi cyclical perturbations in total ozone (quasi-biennial oscil lation – QBO, El Niño–Southern Oscillation – ENSO, and North Atlantic Oscillation – NAO) can be used as indepen dent proxies in evaluating Global Ozone Monitoring Exper iment (GOME) 2 aboard MetOp A (GOME-2A) satellite total ozone data, using ground-based (GB) measurements, other satellite data, and chemical transport model calcula tions. The analysis is performed in the frame of the vali dation strategy on longer time scales within the European Organisation for the Exploitation of Meteorological Satel lites (EUMETSAT) Satellite Application Facility on Atmo spheric Composition Monitoring (AC SAF) project, cover ing the period 2007–2016. Comparison of GOME-2A total ozone with ground observations shows mean differences of about −0.7±1.4 % in the tropics (0–30◦ ), about +0.1±2.1 % in the mid-latitudes (30–60◦ ), and about +2.5 ± 3.2 % and 0.0±4.3 % over the northern and southern high latitudes (60– 80◦ ), respectively. In general, we find that GOME-2A total ozone data depict the QBO–ENSO–NAO natural fluctuations in concurrence with the co-located solar backscatter ultravi olet radiometer (SBUV), GOME-type Total Ozone Essential Climate Variable (GTO-ECV; composed of total ozone ob servations from GOME, SCIAMACHY – SCanning Imag ing Absorption SpectroMeter for Atmospheric CHartogra phY, GOME-2A, and OMI – ozone monitoring instrument, combined into one homogeneous time series), and ground based observations. Total ozone from GOME-2A is well cor related with the QBO (highest correlation in the tropics of +0.8) in agreement with SBUV, GTO-ECV, and GB data which also give the highest correlation in the tropics. The differences between deseazonalized GOME-2A and GB to tal ozone in the tropics are within ±1 %. These differences were tested further as to their correlations with the QBO. publishedVersion